2010
DOI: 10.14429/dsj.60.583
|View full text |Cite
|
Sign up to set email alerts
|

Development of Three-dimensional Grid-free Solver and its Applications to Multi-body Aerospace Vehicles

Abstract: Grid-free solver has the ability to solve complex multi-body industrial problems with minimal effort. Grid-free Euler solver has been applied to number of multi-body aerospace vehicles using Chimera clouds of points including flight vehicle with fin deflection, nose fairing separation of hypersonic launch vehicle. A preprocessor has been developed to generate connectivity for multi-bodies using overlapped grids. Surface transpiration boundary condition has been implemented to model aerodynamic damping and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…It is shown that the simulation code can predict unsafe cases and can be used as an important analysis tool to determine critical flight conditions before carrying out actual flight tests. Recently, hybrid RANS/LES models are employed to predict the store separation from weapons bays 18. In the present work, an integrated store separation dynamics (SSD) tool 19 , that consists of a Grid-free Euler solver, a pre-processor and a RBD code, is used to simulate store separation dynamics of an agile air-to-air missile from a fighter aircraft at various launch conditions. The objective of the present work is to demonstrate that the SSD suite could predict the aircraft flow field effects on the trajectory of an unguided missile launched from the aircraft in flight.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the simulation code can predict unsafe cases and can be used as an important analysis tool to determine critical flight conditions before carrying out actual flight tests. Recently, hybrid RANS/LES models are employed to predict the store separation from weapons bays 18. In the present work, an integrated store separation dynamics (SSD) tool 19 , that consists of a Grid-free Euler solver, a pre-processor and a RBD code, is used to simulate store separation dynamics of an agile air-to-air missile from a fighter aircraft at various launch conditions. The objective of the present work is to demonstrate that the SSD suite could predict the aircraft flow field effects on the trajectory of an unguided missile launched from the aircraft in flight.…”
Section: Introductionmentioning
confidence: 99%
“…By the 1990s [5], it began to be applied to computational fluid dynamics. Large numbers of researches are made by Liu and Su [6], Morinishi [7][8][9], Anandhanarayanan [10,11], and Katz and Jameson [12][13][14] later. The numerical simulation of unsteady flow with moving boundary in meshless method only involves the movement of the discrete points, but not restriction of stretch or distortion of mesh.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with mesh methods, meshless method has more advantages of geometric flexibility in dealing with complex 2 Advances in Mechanical Engineering aerodynamic calculation for complex configuration and complex flow process. Numerical simulation of unsteady flow based on meshless method has been studied by Morinishi [15], Anandhanarayanan [10,11], Wang et al [16], Zhou and Xu [17,18], Wang et al [19,20], and Pu and Chen [21].…”
Section: Introductionmentioning
confidence: 99%
“…[11] for a comparative analysis of popular discretization approaches). Moreover, applications to unsteady problems accounting for body motion have also been explored with success in a meshless context through small perturbation boundary conditions or domain deformation techniques, see for instance [12][13][14]. All in all, meshless features have been increasingly exploited and numerous advantages over conventional discretization techniques have been brought to light.…”
Section: Introductionmentioning
confidence: 99%